(untitled) - Kraut, Edgar A. (Mineola, N.Y., 2007)
this text provides the necessary background in mathematics to study the concepts of electromagnetic theory and quantum mechanics. Topics include vector algebra, matrix and tensor algebra, vector calculus, functions of a complex variable, integral transforms, linear differential equations, and partial differential equations
Phương trình toán lý,Các phương pháp toán Lý
Keywords: Mathematical physics,Toán học vật lý